Employee Engagement in Higher Education: Integrating Organizational Communication and Work Culture Through a Literature Review - Sitanggang, Lestari Pratiwi; Tarigan, Miska Irani Br.; Silalahi, Donalson (Cattleya Darmaya Fortuna, 2026)
The changing strategic environment of higher education, characterized by globalization, the digitalization of academic services, and increasing demands for public accountability, has positioned human resources as a strategic asset for the sustainability of higher education institutions. In this context, employee engagement has become a central issue in human resource management (HRM), as the work engagement of lecturers and administrative staff directly influences the quality of the tridharma of higher education, institutional performance, and academic organizational reputation. This article aims to comprehensively examine the conceptual and empirical relationships among organizational communication, work culture, and employee engagement within the context of higher education institutions. The study employs a structured narrative literature review method using a thematic analysis approach on reputable national and international scholarly articles published between 2014 and 2024. The literature was sourced from Scopus, Web of Science, Emerald Insight, and Google Scholar databases. The findings indicate that employee engagement functions as a psychological mechanism linking HRM practices to the performance of higher education institutions. Open, transparent, and participatory organizational communication has been shown to enhance psychological safety and employee trust, while a value-oriented, collaborative, and adaptive work culture strengthens work meaningfulness and affective commitment. Furthermore, this study identifies research gaps in the context of private higher education institutions and educational organizations in developing countries, thereby recommending the development of a contextualized employee engagement model as a direction for future empirical research.